Plasma lactate at admission does not predict mortality and complications in hip fracture patients: a prospective observational study. (18th August 2018) - Jonsson, Magnus H.; Hommel, Ami; Turkiewicz, Aleksandra; Ekelund, Ulf; Melander, Olle; Englund, Martin; Bentzer, Peter
Abstract: Hip fractures in elderly carry a high mortality. Our objective was to test the hypothesis that plasma lactate concentration at hospital admission can be used to identify patients with a high risk for poor outcome. Hip fracture patients admitted to a university hospital in Sweden from January 2011 to August 2014 in whom a venous lactate was obtained at admission were included in this prospective observational study. Primary outcome measure was 30-d mortality and secondary outcome measure was a composite outcome of 30-d mortality and postoperative complications. Lactate concentration was evaluated as a continuous predictor using logistic regression, crude and adjusted for age, gender and American Society of Anesthesiology Physical Status (ASA PS) score. Discrimination was evaluated using receiver operating characteristics (ROC) analysis. Totally, 690 patients were included. Median age was 84 years (interquartile range [IQR] 77–90). At 30-d follow-up, mortality was 7.2%, and 45% of the patients had suffered the composite outcome. Median lactate level was 1.3 mmol/L (IQR 1.0–1.8 mmol/L). The odds ratio (OR) by each 1.0 mmol/L increase in the lactate concentration for 30-d mortality was 1.13 (95% CI 0.77–1.68) while for the composite outcome it was 1.06 (95% CI 0.85–1.3). Similar results were obtained after adjustment for age, sex and ASA PS classification for both outcomes. Area under the ROC curve for lactate as a predictor of 30-d mortality was 0.51 (95% CI 0.45–0.57). In our cohort, plasma lactate at admission does not appear to be a useful biomarker to identify high-risk patients after hip fracture.